Construct validity of Patient-Reported Outcomes Measurement Information System Paediatric measures in juvenile idiopathic arthritis and systemic lupus erythematosus: cross-sectional evaluation. Issue 1 (27th January 2023) - Weitzman, Elissa R; Gaultney, Amy; von Scheven, Emily; Ringold, Sarah; Mann, Courtney M; Magane, Kara M; Lin, Li; Leverty, Renee; Dennos, Anne; Hernandez, Alexy; Lippmann, Steven J; Dedeoglu, Fatma; et al.
Abstract : Objectives: Evaluate construct validity of Patient-Reported Outcomes Measurement Information System (PROMIS) Paediatric measures of symptoms and functioning against measures of disease activity among youth with juvenile idiopathic arthritis (JIA) or systemic lupus erythematosus (SLE). Design: Cross-sectional associations among PROMIS measures and clinical metrics of disease activity were estimated. Setting: Seven clinical sites of the Childhood Arthritis and Rheumatology Alliance (CARRA) in the USA. Participants: Youth aged 8–17 years enrolled in the CARRA Registry. Intervention: PROMIS measures were collected and associations with clinical measures of disease activity estimated, by condition, in bivariate and multivariable analyses with adjustment for sociodemographics, insurance status, medications and disease duration. Main outcome measures: PROMIS Paediatric measures of mobility, physical activity, fatigue, pain interference, family relationships, peer relationships, depressive symptoms, psychological stress, anxiety, and meaning and purpose, and clinical metrics of disease. Results: Among 451 youth (average age 13.8 years, 71% female), most (n=393, 87%) had a JIA diagnosis and the remainder (n=58, 13%) had SLE. Among participants with JIA, those with moderate/high compared with low/inactive disease had, on average, worse mobility (multivariable regression coefficient and 95% CIs) (−7.40; −9.30 to –5.50), fatigue (3.22; 1.02 to 5.42), pain interference (4.76; 3.04 to 6.48), peer relationships (−2.58; −4.52 to –1.64), depressive symptoms (3.00; 0.96 to 5.04), anxiety (2.48; 0.40 to 4.56) and psychological stress (2.52; 0.68 to 4.36). For SLE, youth with active versus inactive disease had on average worse mobility (−5.07; −10.15 to 0.01) but PROMIS Paediatric measures did not discriminate participants with active and inactive disease in adjusted analyses. Conclusions: Seven PROMIS Paediatric measures discriminated between active and inactive disease in youth with JIA. Results advance the usefulness of PROMIS for understanding well-being and improving interventions for youth with JIA, but larger studies are needed to determine utility in SLE cohorts. Trial registration number: National Institute of Arthritis and Musculoskeletal and Skin Diseases (U19AR069522).